Authorial documentary filmmaking in Ukraine in the late 1980 to early 1990 s : between political awakening and national identity - Demydenko, Maksym; Konovalov, Dmytro; Konovalova, Sofiia; Ostrous, Stanislav; Markhaichuk, Nataliia (РДГУ, 2025)
The article explores the transformation of Ukrainian documentary cinema during the late 1980s to early 1990s–an essential period marked by the collapse of Soviet ideological control and the rise of national consciousness. It focuses on the emergence of author documentary filmmaking as a response to newly accessible, previously suppressed subjects, including political repression, the Holodomor, Chornobyl, Ukrainian dissidence, and distorted historical narratives. A central feature of this transformationwas the application of kino-pravda(film-truth) –a technique pioneered by Dziga Vertov –where subjective observation, minimal mediation, and immersion in real events replaced traditional propagandistic cliché. Films such as Steps of Democracy, July Thunderstorms, and Chornobyl: Chronicle of Difficult Weeksillustrate how Ukrainian filmmakers adopted these methods to reconstruct public memory and challenge official narratives. The article underscores the importance of documentary cinema not only as a medium of filming historical events but also as a powerful cultural instrument in constructing national identity. Through its capacity to interpret collective trauma, articulate suppressed voices, and reflect the evolving societal values of an emerging independent Ukraine, documentary film became a powerful tool for national self-definition. Future research should further examine the role of documentary cinema in constructing Ukrainian post-Soviet national narratives and its long-term influence on cultural memory and identity formation.

Досліджено трансформації українського документального кінематографу на зламі 1980–1990-х років ХХ століття в контексті проблематики національної ідентичності. Проаналізовано основні тематичні напрями, що стали актуальними для авторського висловлювання в період ідеологічної кризи та «перебудови»: Чорнобильська катастрофа, шахтарські протести, суспільно-політичні зрушення, осмислення радянських репресій та розсекречення історичних сюжетів. Виявлено художньо-документальні засоби, через які кінематографісти відходили від пропагандистського формату радянської агітдокументалістики та зверталися до авторського погляду, інтерпретаційності та наративної відкритості. Висвітлено, що в цей період документальне кіно стає майданчиком візуального репрезентування національної ідентичності та колективної історичної пам’яті.
Keywords: документальне кіно; аудіовізуальне мистецтво; audiovisual culture; film and television art; documentary film; Ukrainian cinema; кіномистецтво українське